The genome of Salmonella enterica serovar Typhi. - Baker, S; Dougan, G (2007)
The generation of complete genome sequences provides a blueprint that facilitates the genetic characterization of pathogens and their hosts. The genome of Salmonella enterica serovar Typhi (S. Typhi) harbors ~5 million base pairs encoding some 4000 genes, of which >200 are functionally inactive. Comparison of S. Typhi isolates from around the world indicates that they are highly related (clonal) and that they emerged from a single point of origin ~30,000-50,000 years ago. Evidence suggests that, as well as undergoing gene degradation, S. Typhi has also recently acquired genes, such as those encoding the Vi antigen, by horizontal transfer events.